Montreal Cognitive Assessment (MoCA) - Gonçalves, Juliana Mendes (2021)
The Montreal Cognitive Assessment (MoCA) is an important brief cognitive screening instrument that is known for its good psychometric properties and sensitivity to detect mild cognitive impairment (MCI). After ten years, it became relevant to update the previous Portuguese normative study due to changes in the population and some limitations present in the study itself. The MoCA was applied to 860 cognitively healthy adults, stratified according to sociodemographic variables verified in the Portuguese population. The new normative data were defined considering the strata of the variables age and educational level, as these showed to have a large effect size on MoCA scores.